Developing communicative competence: Methodological considerations for conducting qualitative research with Spanish-speaking adult learners - Esther Prins; Ana Guisela Chupina (Adult Education Research Conference, 2006)
This article analyzes how we responded to socio-linguistic challenges in our research with Spanish-speaking adults in the U.S. and El Salvador. Our respective racial/ethnic identities, first language, and insider or outsider status created distinctive challenges and communicative strategies. We argue that cross-cultural researchers must recognize socio-linguistic variation within groups and develop communicative competence.
Keywords: communicative competente; cross-cultural research; international adult education; socio-linguistic analysis; Spanish